A model β-sheet interaction and thermodynamic analysis of β-strand mimetics. Issue 27 (19th June 2015) - Robinson, Colin W.; Rye, Carl S.; Chessum, Nicola E. A.; Jones, Keith
Abstract : Two novel β-strand mimetics are synthesized and their binding to a model peptide is studied in detail by 1 H NMR. Abstract : β-Sheet mediated protein–protein interactions are involved in key signalling pathways in diseases such as cancer. We present small molecule β-strand mimetics and investigate their interactions with a model tripeptide. Using 1 H NMR, the thermodynamic parameters for their binding are determined. These give insight into this biologically important interaction.